C-Peptide Inhibits Decidualization in Human Endometrial Stromal Cells via GSK3β-PP1 - Khaliq, Sana Abdul; Baek, Mi-Ock; Cho, Hye-Jeong; Chon, Seung Joo; Yoon, Mee-Sup (Frontiers in Cell and Developmental Biology, 2020)
Decidualization refers to the functional differentiation of endometrial stromal cells and plays a significant role in embryo implantation and pregnancy. C-peptide is excreted in equimolar concentrations as that of insulin during the metabolism of proinsulin in pancreatic beta-cells. High levels of C-peptide are correlated with hyperinsulinemia and polycystic ovarian syndrome, which show a defect in decidualization. However, the role of C-peptide in decidualization has not yet been studied. Here, we identified C-peptide as an endogenous antideciduogenic factor. This inhibitory function was confirmed by the reduced expression of decidual markers, including prolactin, insulin-like growth factor-binding protein-1, and Forkhead box protein O1 as well as by the fibroblastic morphological change in the presence of C-peptide. C-peptide also enhanced cellular senescence and decreased the proportion of apoptotic cells during decidualization. In addition, C-peptide potentiated the inhibitory effects of both insulin and palmitic acid in an AKT- and autophagy-independent manner, respectively. Furthermore, C-peptide augmented protein phosphatase 1 (PP1) activity, leading to a reduction in the inhibitory phosphorylation of glycogen synthase kinase (GSK)3β, which resulted into enhanced cellular senescence and decreased apoptosis during decidualization. Taken together, our findings suggest that C-peptide is an antideciduogenic factor acting via the regulation between PP1 and GSK3β in patients with hyperinsulinemia.